Postoperative Infection: Prevention, Diagnosis, and Treatment Guidelines for the Sports Surgeon. Issue 1 (March 2022) - Pullen, W. Michael; Money, Adam J.; Ray, Taylor E.; Freehill, Michael T.; Sherman, Seth L.
Abstract : Postoperative infection remains a potentially devastating complication facing the sports medicine surgeon. Infection prevention begins with a thorough history and physical examination to identify patient specific risk factors and aid in risk stratification. Perioperative steroid injections should be used cautiously, with increased time prior to or following surgery being associated with lower infection risk. Sterile preparation with an alcohol containing solution is typically preferred, though there is limited evidence to identify which product is superior. Diagnosis can be challenging with a high index of suspicion needed to identify and appropriately manage patients. Treatment involves prompt irrigation and debridement with deep cultures. Antibiotic coverage should begin with empiric broad treatment and be tailored based on culture results. Early consultation with an infectious disease specialist is recommended to ensure appropriate antibiotic coverage and duration of treatment.